2006
DOI: 10.1161/01.atv.0000247243.48542.9d
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cells in Atherosclerosis Originate From the Local Vessel Wall and Not Circulating Progenitor Cells in ApoE Knockout Mice

Abstract: Objective-Recent studies of bone marrow (BM)-transplanted apoE knockout (apoE Ϫ/Ϫ ) mice have concluded that a substantial fraction of smooth muscle cells (SMCs) in atherosclerosis arise from circulating progenitor cells of hematopoietic origin. This pathway, however, remains controversial. In the present study, we reexamined the origin of plaque SMCs in apoE Ϫ/Ϫ mice by a series of BM transplantations and in a novel model of atherosclerosis induced in surgically transferred arterial segments. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
5
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(168 citation statements)
references
References 29 publications
8
151
5
1
Order By: Relevance
“…To further investigate the potential role of XBP1 splicing in atherosclerosis development, spliced XBP1 was overexpressed by adenoviral gene transfer in ECs in the straight part of blood vessels to mimic high levels of spliced XBP1 in branch areas. Artery isograft is an appropriate model to study EC function in atherosclerosis, as the isograft itself does not induce lesion development (33). In this model, a monolayer of endothelial cells was found in grafted vessels 4 weeks after grafting (Fig.…”
Section: Overexpression Of Spliced Xbp1 Induces Atherosclerosis In Anmentioning
confidence: 99%
“…To further investigate the potential role of XBP1 splicing in atherosclerosis development, spliced XBP1 was overexpressed by adenoviral gene transfer in ECs in the straight part of blood vessels to mimic high levels of spliced XBP1 in branch areas. Artery isograft is an appropriate model to study EC function in atherosclerosis, as the isograft itself does not induce lesion development (33). In this model, a monolayer of endothelial cells was found in grafted vessels 4 weeks after grafting (Fig.…”
Section: Overexpression Of Spliced Xbp1 Induces Atherosclerosis In Anmentioning
confidence: 99%
“…More recently, Bentzon et al 31 reported that they could not replicate the results of Sata et al 6 and provided strong evidence that hematopoietic stem cells did not contribute to smooth muscle cells in the fibrous cap of atherosclerotic/arterial transplant atherosclerosis lesions in a chronic (more than 20 weeks) mouse model. This is consistent with our current study that GFP could not be detected in smooth muscle cells at longer time points (16 weeks) by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 97%
“…However, in a murine model of allograft vasculopathy, which is primarily characterized by smooth muscle proliferation, Hagensen et al found no contribution of circulating cells [36], questioning the paradigm of BM-derived smooth muscle progenitors. Similarly, in young or old Apoe-null mice the contribution of BM-derived cells appeared to be very small or negligible [102][103][104]. Such controversy is probably related to methodological issues inherent to the experimental model used, because apolipoprotein E (ApoE) itself has been shown to regulate BM-stem progenitor cell trafficking (critically discussed in [99]).…”
Section: Monocyte-macrophage Polarisationmentioning
confidence: 99%